If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + -5 = 3a + -15 Reorder the terms: -5 + 2a = 3a + -15 Reorder the terms: -5 + 2a = -15 + 3a Solving -5 + 2a = -15 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -5 + 2a + -3a = -15 + 3a + -3a Combine like terms: 2a + -3a = -1a -5 + -1a = -15 + 3a + -3a Combine like terms: 3a + -3a = 0 -5 + -1a = -15 + 0 -5 + -1a = -15 Add '5' to each side of the equation. -5 + 5 + -1a = -15 + 5 Combine like terms: -5 + 5 = 0 0 + -1a = -15 + 5 -1a = -15 + 5 Combine like terms: -15 + 5 = -10 -1a = -10 Divide each side by '-1'. a = 10 Simplifying a = 10
| 9b^2+15b-14=0 | | 42-r-2(13-5r)+7=85 | | 3x^2+90x=180 | | w+6=334 | | (x-5)-4(x-6)=9 | | 16x^4-5x^2-11=0 | | -3.2x=8.48 | | (1/8)(5y+64)=.25(20+2y) | | 3x=-2.25 | | 334=w(w+6) | | [36]/3= | | -1-15=-3t+t | | 2g=g+5 | | [36]3= | | 6+2(3j-2)=4(1-j) | | 5x-10+3x=7+8x-17 | | x+x+2+x+4+x+6=188 | | -16t^2+484= | | 4x-x+6=3x-2+6 | | w^3-5w^2-14w=0 | | 6(4-2x)=3(4x+8) | | 12+2x=4x/4+2x | | 0=12.5x-4.9x^2 | | -(8y+3)-(-7y-7)=-2 | | -3p-4=2p | | a+3-4=-1 | | -5+13x=-6x^2 | | -9v=27 | | 48-(12)= | | 3(c-22)=2(c-6) | | r^2+2r-7=0 | | 3.7=.21w |